The Implementation of Green Marketing in SMEs as an Effort to Enter the International Market (Case Study of Creabrush Indonesia) - Sulton Sholehuddin; Sudarmiatin, Sudarmiatin (Cita konsultindo, 2024)
Green Marketing is a marketing activity that focuses on environmental sustainability. This research was conducted with consideration of the importance for every business actor to implement Green Marketing in their business activities, especially those oriented towards export. One example of a business that applies Green Marketing is the Creabrush MSME. The purpose of this study is to describe the implementation of Green Marketing in Creabrush MSME as an effort to enter the international market, explain the factors influencing the management of Creabrush MSME in implementing Green Marketing, determine the competitive advantages held by Creabrush MSME in applying Green Marketing, as well as the impact of that implementation. This research is descriptive in nature with a qualitative approach. The author conducted interviews with the owners and employees of Creabrush MSME to find out how Green Marketing is implemented in that MSME. The data analysis technique used is Miles and Huberman's data analysis technique. The results of the study indicate that the application of Green Marketing in Creabrush MSME is already environmentally friendly in terms of production, promotion, distribution, and pricing activities. Awareness of environmental responsibility, government regulations, competition in similar industries, and cost savings in waste management are factors that influence the implementation of Green Marketing in Creabrush MSME.